BUSINESS DEVELOPMENT IN KAZAKHSTAN AT THE END OF THE XIX – AT THE BEGINNING OF THE XX CENTURY (ON THE EXAMPLE OF SEMIPALATINSK REGION) - Raushan, Akhmetova (European Scientific Journal, ESJ, 2014)
The article discusses the features of the development of capitalist relations in Kazakhstan as a colony of the Russian empire, the adaptation of the Kazakh population to the new conditions of the economy, the emergence of new forms of capital investment, private entrepreneurship.